The Addams family 2 [videorecording (DVD)] - Vernon, Conrad; Hernandez, Dan; Samit, Benji; Queen, Ben; Fogel, Susanna (Universal Pictures Home Entertainment, 2021)
The Addams get tangled up in more wacky adventures and find themselves involved in hilarious run-ins with all sorts of unsuspecting characters. Sequel to the 2019 animated film, 'The Addams Family'.